Economy of Balochistan: Potentials and Constraints across National Boundaries - Karimzadeh, Majid; Eidouzehi, Emam Bakhsh Tireh (IJRDO - Journal of Social Science and Humanities Research, 2018)
Recently, border regions and border effects attract a lot of interest in political practice and economic research. Substantial interest in regions located along the frontiers of integrating countries is predominantly inspired by the opinion that their specific geographic position might cause peculiarities in economic adjustments. There are important contrasts between Balochistan and the rest of Iran and Pakistan in terms of comparative advantages and potential sectors. While the rest of Iran and Pakistan are labour-abundant economy with potential growth modes in agriculture, manufacturing as well as labour-intensive service sectors, Balochistan is relatively scarce in agricultural growth and industrial investment. Balochistan offers some of the best assets for development. Balochistan is generously donated with natural and locational resources.